p53 and E2F-1 cooperate to mediate apoptosis. - Wu, X (1994)
The tumor-suppressor protein p53 appears to function at the G1 phase of the cell cycle as a checkpoint in response to DNA damage. Mutations in the p53 gene lead to an increased rate of genomic instability and tumorigenesis. The E2F-1 transcription factor is a protein partner of the retinoblastoma-susceptibility gene product, RB. E2F-1 appears to function as a positive regulator or signal for entry into S phase. To explore possible interactions of p53 and E2F-1 in the cell cycle, a human E2F-1 expression plasmid was introduced into a murine cell line containing a temperature-sensitive p53 allele which produces a p53 protein in the wild-type conformation at 32 degrees C and the mutant form at 37.5 degrees C. Coexpression of the wild-type p53 protein and E2F-1 in these cells resulted in a rapid loss of cell viability through a process of apoptosis. Thus, the cell cycle utilizes an interacting or communicative pathway between RB-E2F-1 and p53.